Infrared spectroscopy of ion-induced cross-linked sulfonated poly(ether ether ketone). (14th June 2016) - Anderson, Kierstyn; Kingston, Erin; Romeo, Joseph; Doan, Jonathan; Loupe, Neili; Dimakis, Nicholas; Smotkin, Eugene S.
Abstract: The dehydration of SPEEK-[H] (protonated sulfonated poly(ether ether ketone)) converts 3-fold symmetric (C3V ) hydrated sulfonate sites to sulfonic acid sites with no local symmetry (C1 ). Like Nafion-[H], SPEEK-[H] C3V and C1 environments afford IR group modes (C3V, HF (1087 cm −1 ); C3V, LF (1026 cm −1 ) and C1, HF (1362 cm −1 ); C1, LF (904 cm −1 )) due to the mechanical coupling of vibrational internal coordinates of an ether link with those of the sulfonate or sulfonic acid exchange site. C3V and C1 bands are inversely correlated during membrane hydration/dehydration. Hydrated SPEEK-[M] (M: Cu 2+, Ni 2+, Cd 2+, Pb 2+, Sr 2+ or Ba 2+ ) exhibits SPEEK-[H] C3V bands because cation waters of hydration preclude binding to the hydrated exchange site. When cation hydration spheres are thermally stripped at high vacuum, SPEEK-[M] C3V bands supplant SPEEK-[H] C3V bands, inducing SPEEK cross-linking. Incomplete cross-linking is evidenced by low intensities of SPEEK-[M] C1, HF bands. The 1362 cm −1 band intensities are inversely correlated with cation hydration enthalpies. Graphical abstract: Highlights: Hydration dependent IR spectra of ion exchanged sulfonated poly (ether ether) ketone. Infrared normal mode assignments based on SPEEK exchange site point group symmetry. SPEEK dehydration shifts local symmetry from C3V (sulfonate) to C1 (sulfonic acid). Dehydration of divalent ion exchanged SPEEK induces non-covalent crosslinking. Degree of ion induced crosslinking inversely correlated to cation hydration enthalpy.